Body sway and performance at competition in male pistol and rifle Olympic shooters - Mon, D.; Zakynthinaki, M.; Cordente, C.; Barriopedro, M.; Sampedro, J. (Biomedical Human Kinetics, 2014)
We examine the body sway differences between a) pistol and rifle and b) elite and national level senior male Olympic shooters, as well as the possible relation between body sway and performance at competition in Olympic shooting. Material and methods: Two body sway tests (feet together and feet apart) were performed by 28 Spanish male senior Olympic shooters just before competition. Performance was measured as the actual score at competition. Total center of mass (COM) areas and average/maximum COM velocities were calculated from force platform data. ANCOVA tests were implemented with age as a covariable. The non-parametric test U of Mann Whitney was used to study the differences between national and elite shooters. Pearson correlations were used to examine the relation between performance and total COM area. Results: At the feet apart position, rifle and elite shooters were found to have statistically less body sway than pistol and national level shooters respectively (total COM areas: F1,25 = 6.7; p < 0.05, and Z = 2.36; p < 0.01). No statistically significant differences were found regarding the feet together position, regardless the level or discipline (total COM areas: F1,25 = 1.49 ; p > 0.05; 1 - ß = 0.22, average COM velocities: F1,25 = 0.58; p > 0.05; 1 - ß = 0.11, maximum COM velocities: F1,25 = 0.03; p > 0.05; 1 - ß = 0.05). No significant relation was found between body sway and performance at competition (feet together: r = 0.13, feet apart: r = 0.14, p > 0.05). Age and body sway were not found to be significantly correlated (F1,25 = 0.23; p > 0.05; 1 - ß = 0.08). Conclusions: Easy